Voila!: The Rockefeller Archive Center's Exhibit Creation Process. Issue 1 (March 2018) - Vassari, Marissa
The Rockefeller Archive Center (RAC) in Sleepy Hollow, New York, hosts groups ranging from foundation staff to college-level classes. Over the course of a year, the RAC hosts approximately 30 visiting groups that include from as few as 10 people to as many as 45. The aim is to engage visiting groups with the RAC's vast collections by creating hands-on, tailored exhibits. The RAC has created policies and procedures, exhibit guides, and workflow templates that allow for documentation of each exhibit and encourage inclusiveness and transparency among staff. Employing a new, standardized approach by using these tools has made all phases of the exhibit process more efficient and allows the RAC to provide a rich, immersive archival experience for visitors. This article offers a case study in standardized exhibit creation that may benefit professionals in other institutions who are seeking to develop work processes and policies without diminishing the visitor experience.